Morocco : First Review Under the Arrangement Under the Precautionary and Liquidity Line-Press Release; Staff Report; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Morocco's First Review under the Arrangement under the Precautionary and Liquidity Line (PLL). Morocco's economic fundamentals and policy frameworks are sound. The country is implementing well-constructed policies and remains committed to maintaining such policies in the future. The September 2016 quantitative indicative targets (ITs) were met. The end-March 2017 fiscal deficit ITs were met, but the end-March 2017 reserves ITs were missed owing to the widening current account deficit since July 2016. The authorities have not drawn on the arrangement and continue to treat it as precautionary. The IMF staff recommends the completion of the first review under the PLL arrangement.